El parque y la plaza: geometrías bajo el cielo. (2006)
Jay Pritzker Pavillon. <Chicago>, por F. Gehgy.- Memorial. <Berlín>, P. Eisenman.
Keywords: GEHRY, FRANK O; ESTADOS UNIDOS; PARQUES; AUDITORIOS; EISENMAN, PETER; ALEMANIA; MONUMENTOS